REAL-TIME ULTRASONIC LOCALIZATION USING AN ULTRASONIC SENSOR ARRAY (Perner's Contacts, 2012)
This paper addresses localization using an ultrasonic receive array. The localization is realized in real-time. It is shown, that this method leads to good angle estimation accuracy in a low-cost indoor system.
Keywords: localization, ultrasound, ultrasound sensor array